Large newly built ship-bathing facility next to the Chain Bridge on the Prater side - Zinke, Johann Wenzel, 1797-1858 (artist):::Creator:::::::::::: (Bureau der Theaterzeitung; Austria; Vienna)
Color engraving of the Schiffbad in the Prater